2021
DOI: 10.37506/ijfmt.v15i3.15909
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Asphyxia as a Risk Factor for Sensorineural Hearing Loss in Indonesian Children

Ratna Anggraeni,
Wijana,
Pudyastuti Rachyanti

Abstract: Background: Neonatal Asphyxia is one of the risk factors for hearing loss in children. Neonatal Asphyxia causes cochlear damage due to lack of oxygenation and tissue perfusion which can lead to cell death. Objective: Determining the risk of Neonatal Asphyxia for the occurrence of sensorineural hearing loss in children. Methods: A case control study was done between July to September 2020. Children with sensorineural hearing loss are on study group and the control group is children with normal hearing. Particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Our study on the most common causes of hearing loss concurs with similar studies in literature. [8][9][10][11][12] Other causes included genetics, familial, jaundice, infections and unknown aetiologies. Among the candidates implanted one was a case of Waardenburg and the other incomplete partition of cochlear type 3 (IPT3) which suggested genetic mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Our study on the most common causes of hearing loss concurs with similar studies in literature. [8][9][10][11][12] Other causes included genetics, familial, jaundice, infections and unknown aetiologies. Among the candidates implanted one was a case of Waardenburg and the other incomplete partition of cochlear type 3 (IPT3) which suggested genetic mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal, fetal, placental, and neonatal complications like hypo/hypertensive disorders, hypoxia induced by cardiopulmonary diseases, anemia, diabetes, persistent epilepsy, the placenta or umbilical cord accidents, congenital anomalies, chorioamnionitis, and infections are the main risk factors of asphyxia [1,4,5]. Despite several investigations reporting the prevalence of asphyxia in developed and developing countries [5,6,9,10], very few studies from Iran [11][12][13] have demonstrated the rate of neonatal asphyxia and its affecting factors. Hence, considering neonatal asphyxia as an important cause of mortality and morbidity, this study aimed to determine the prevalence of asphyxia, its consequences, and neonatal outcomes among Iranian term and late preterm live-born neonates.…”
Section: Introductionmentioning
confidence: 99%